Olive mill wastewater valorization : use by non-conventional yeasts - Gonçalves, Cristiana (2008)
The ability of the strains Yarrowia lipolytica and Candida rugosa to grow on Olive Mill Wastewater (OMW) based medium and to produce high-value compounds from OMW (such as enzymes), while degrading this waste, was tested. Factors affecting cellular growth and OMW degradation were also studied, such as OMW composition, dilution and supplementation. OMW collected from 3-phase olive mill of the north region of Portugal were used and characterized chemical and biochemically. OMW with COD ranging from 100 g·L-1 to 200 g·L-1 were supplemented with yeast extract and ammonium chloride proportionally to its organic composition. Preliminary studies of OMW consumption were carried out in batch cultures of Y. lipolytica W29 and C. rugosa PYCC 3238. The strains were able to grow in the OMW used without dilution, to consume almost all of the sugars present in the media and to significantly reduce COD. Y. lipolytica W29 was less affected by operating conditions changes such as, stirring rate variation and OMW medium supplementation.